Performance Analysis of Ultra-Wideband Channel for Short-Range Monopulse Radar at Ka-Band - Naohiko Iwakiri; Natsuki Hashimoto; Takehiko Kobayashi (Journal of Electrical and Computer Engineering)
High-range resolution is inherently provided with Ka-band ultra-wideband (UWB) vehicular radars. The authors have developed a prototype UWB monopulse radar equipped with a two-element receiving antenna array and reported its measurement results. In this paper, a more detailed verification using these measurements is presented. The measurements were analyzed employing matched filtering and eigendecomposition, and then multipath components were extracted to examine the behavior of received UWB monopulse signals. Next, conventional direction finding algorithms based on narrowband assumption were evaluated using the extracted multipath components, resulting in acceptable angle-of-arrival (AOA) from the UWB monopulse signal regardless of wideband signals. Performance degradation due to a number of averaging the received monopulses was also examined to design suitable radar's waveforms.